2022
DOI: 10.2147/ijnrd.s286947
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Hemodialysis: What We Know so Far

Abstract: Traditionally, patients that develop progressive chronic kidney disease in need of kidney replacement therapy are prescribed thrice weekly in-center hemodialysis sessions at the beginning of therapy. This empiric prescription is based on historic trials that were comprised of mostly prevalent patients. Incremental hemodialysis is the process of performing <3 sessions of dialysis per week or limiting dialysis dose by duration at the initial onset of treatment to provide a more gradual transition, mimicking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
2
0
2
Order By: Relevance
“… 43 - 45 Approaches to incremental dialysis can also help reduce waste generation. 46 , 47 Cultivating local expertise and generating guidelines to inform other HCPs can help champion ESKC.…”
Section: Policy and Practice Implicationsmentioning
confidence: 99%
“… 43 - 45 Approaches to incremental dialysis can also help reduce waste generation. 46 , 47 Cultivating local expertise and generating guidelines to inform other HCPs can help champion ESKC.…”
Section: Policy and Practice Implicationsmentioning
confidence: 99%
“…There is renewed interest in incremental dialysis, which is defined as HD administered less than thrice weekly or limiting dialysis prescription by duration to allow for a more gradual transition. 91 This approach addresses patient concerns about the potential loss of independence and ability to work when adhering to a conventional haemodialysis regimen. A recent Australian study among individuals who were either presently undergoing HD or on the verge of starting demonstrated that all 26 participants preferred an incremental approach to HD.…”
Section: Human-centred Care As a Model To Address Unmet Needs In Chro...mentioning
confidence: 99%
“…En DP, il ne fait aucun doute que les régimes incrémentiels, en réduisant le nombre d'échanges de DPCA et en adaptant le volume intrapéritonéal en fonction de la surface corporelle et des besoins d'épuration, favorisent définitivement une meilleure perception de la qualité de vie par le patient, ce qui fait converger les gains cliniques et économiques. En revanche, en hémodialyse, il convient de se demander si la dialyse incrémentale est conçue pour réduire les coûts et la charge des séances ou pour adapter la prescription en fonction des besoins biologiques [47].…”
Section: Utilisation Des Régimes De Dialyse Incrémentaleunclassified
“…De plus, dans d'autres conditions cliniques, l'HD peu fréquente peut être inappropriée pour les patients présentant une prise de poids inter-dialytique élevée, même si la clearance résiduelle rénale de l'urée est en faveur d'une dialyse incrémentale [51]. Cet aspect est critique et pourrait bien expliquer le pic de mortalité et d'événements indésirables rapportés après le début de l'hémodialyse, en particulier chez les patients plus âgés, qui sont plus enclins aux atteintes cardiaques induites par l'hémodialyse [46,47]. Les taux d'ultrafiltration élevés, l'hypotension intra-dialytique et les lésions ischémiques associées sont une préoccupation chez les patients congestifs et chez ceux qui présentent une prise de poids inter-dialytique élevée [52,53].…”
Section: Les Obstacles Et Les Inconvénients Potentielsunclassified